Nematode Management Using Sorghum and Its Relatives - Zane Joseph Grabau (EDIS)
Sorghum and sorghum-sudangrass are often used in crop rotation systems in Florida. They produce a source of forage or silage for animal feed, and many cultivars are effective in reducing population levels of root-knot nematodes, which are key nematode pests in Florida as well as many other parts of the world. This article is intended to guide agricultural professionals in making decisions about producing sorghum and its relatives for nematode management.